SIMULATION MODELS OF PEDESTRIAN FLOW (Perner's Contacts, 2011)
This paper introduces some of the mathematical models of pedestrian flow – their basic principles and using in the simulations. In the end working with one of the simulation programs is described.
Keywords: simulation; pedestrian flow; social force model; SimWalk